PENDIDIKAN KADER DAI BERBASIS MASJID: IMPLEMENTASI PADA SEKOLAH DAI AZURA (SADAR) MASJID ASURA DESA KEMANG KECAMATAN KEMANG KABUPATEN BOGOR - Samsuddin; Agusman (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
Mosque-based preacher cadre education is a strategic effort to produce preachers who are strong in intellectual, physical, spiritual, and financial aspects. This study aims to evaluate the implementation of the Mosque-based Dai Cadre Education program at the Azura Dai School (SADAR), Azura Mosque, Bogor Regency, in shaping preachers who are both scientifically competent and effective in their preaching. The research focuses on providing Sharia knowledge, enhancing the quality of da'wah, and strengthening ukhuwah (brotherhood) and networks among preachers. A descriptive qualitative method was used to gather data through interviews, observation, and documentation. Although no graduates have yet been produced, significant progress has been observed in participants' mastery of Sharia knowledge and preaching skills. Interaction within the mosque environment also fosters stronger bonds of brotherhood. The main challenges lie in ensuring the program’s sustainability until graduates are produced and in garnering broader support. Overall, the Azura Dai School demonstrates great potential in developing preachers strong in knowledge, da'wah, and ukhuwah (brotherhood).